NEW DATA ON THE TECTONICS AND STRUCTURE OF THE SEDIMENTARY COVER OF THE WHITE SEA RIFT SYSTEM - Zhuravlev V.A.; Shipilov E.V. (My University, 2007)
The White Sea is an inner sea of Russia, and its geology and geophysics are poorly studied. According to current ideas, rift structures of the Mezen syneclise extend to the White and Barents seas and bend round the Kola Peninsula in the southwest and northeast. Until the present time, these ideas were based only on fragmentary data of the analysis of potential geophysical fields and mainly on materials of the geology of land framing. The analysis of new marine CMP SR, gravity and magnetic survey, and continuous seismic profiling data obtained in 2003 and 2004 (MAGE) in combination with the results of geological and geophysical works on land allowed us to characterize for the first time the inner structure of the White Sea rift system.